Механизм диффузии бора, хрома и титана при одновременном многокомпонентном поверхностном легировании железоуглеродистых сплавов - Гурьев, А. М.; Иванов, С. Г. (НТУ "ХПИ", 2011)
Рассмотрены механизмы совместной диффузии атомов бора, хрома и титана в поверхность стали при комплексном легировании ее этими элементами. Дано объяснение этим явлениям с точки зрения управления течением процесса и получения диффузионных слоев с требуемыми свойствами.

Mechanisms of joint diffusion of atoms of a pine forest, chrome and the titan in a surface of steel are considered at complex alloying by its these elements. The explanation is given to these phenomena from the point of view of management of current of process and reception diffusion layers with demanded properties.
The mechanism of diffusion of the pine forest, chrome and the titan at simultaneous multicomponent superficial alloying iron-carbon alloys
Keywords: диффузионный слой; химико-термическая обработка; борирование; reception diffusion layers; surface of steel; joint diffusion